Accumulation potential and tolerance response of Typha latifolia L. under citric acid assisted phytoextraction of lead and mercury. (October 2020) - Amir, Waqas; Farid, Mujahid; Ishaq, Hafiz Khuzama; Farid, Sheharyaar; Zubair, Muhammad; Alharby, Hesham F.; Bamagoos, Atif A.; Rizwan, Muhammad; Raza, Nighat; Hakeem, Khalid Rehman; Ali, Shafaqat
Abstract: Chelate-assisted phytoextraction by high biomass producing macrophyte plant Typha latifolia L. commonly known as cattail, is gaining much attention worldwide. The present study investigated the effects of Lead (Pb) and Mercury (Hg) on physiology and biochemistry of plant, Pb and Hg uptake in T. latifolia with and without citric acid (CA) amendment. The uniform seedlings of T. latifolia were treated with various concentrations in the hydroponics as: Pb and Hg (1, 2.5, 5 mM) each alone and/or with CA (5 mM). After four weeks of treatments, the results revealed that Pb and Hg significantly reduced the plant agronomic traits as compare to non-treated plants. The addition of CA improved the plant physiology and enhanced the antioxidant enzymes activities to overcome Pb and Hg induced oxidative damage and electrolyte leakage. Our results depicted that Pb and Hg uptake and accumulation by T. latifolia was dose depend whereas, the addition of CA further increased the concentration and accumulation of Pb and Hg by up to 22 & 35% Pb and 72 & 40% Hg in roots, 25 & 26% Pb and 85 & 60% Hg in stems and 22 & 15 Pb and 100 & 58% Hg in leaves respectively compared to Pb and Hg treated only plants. On other hand, the root-shoot translocation factor was ≥1 and bioconcentration factor was also ≥2 for both Pb & Hg. The results also revealed that T. latifolia showed greater tolerance towards Hg and accumulated higher Hg in all parts compared with Pb. Graphical abstract: Image 1 Highlights: Lead and Hg ecotoxicity altered physiological and biochemical functions. Citric acid improved antioxidant defense system and photosynthetic pigments. Citric acid alleviates Pb and Hg stress and enhanced plant growth and biomass. Citric acid enhanced uptake and accumulation of Pb and Hg in Typha latifolia .